Marital status, labour force activity and mortality: A study in the USA and six European countries. Issue 5 (July 2015) - Van Hedel, Karen; Van Lenthe, Frank J.; Avendano, Mauricio; Bopp, Matthias; Esnaola, Santiago; Kovács, Katalin; Martikainen, Pekka; Regidor, Enrique; Mackenbach, Johan P.
Aims: Labour force activity and marriage share some pathways through which they potentially influence health. In this paper, we examine whether marriage and labour force participation interact in the way they influence mortality in the USA and six European countries. Methods: We used data from the US National Health Interview Survey linked to the National Death Index, and national mortality registry data for Austria, England/Wales, Finland, Hungary, Norway and Spain (specifically, the Basque country) during 1999–2007, for men and women aged 30–59 years at baseline. We used Poisson regression to estimate both the additive (relative excess risk due to interaction) and multiplicative interactions between marriage and labour force activity on mortality. Results: Labour force inactivity was associated with higher mortality, but this association was stronger for unmarried, rather than married, individuals. Likewise, being unmarried was associated with higher mortality, but this association was stronger for inactive than for active individuals. To illustrate, among US women out of the labour force, being unmarried was associated with a 3.98 times (95%CI 3.28–4.82) higher risk of dying than being married; whereas the relative risk (RR) was 2.49 (95%CI 2.10–2.94), for women who were active in the labour market. Although this interaction between marriage and labour force activity was only significant for women on a multiplicative scale, there was a significant additive interaction for both men and women. The pattern was similar across all countries. Conclusions: Marriage attenuated the increased mortality risk associated with labour force inactivity; while labour force activity attenuated the mortality risk associated with being unmarried. Our study emphasizes the importance of public health and social policies that improve the health and well-being of unmarried and inactive men and women.